2020
DOI: 10.46234/ccdcw2020.033
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of 2019-nCoV from a Stool Specimen of a Laboratory-Confirmed Case of the Coronavirus Disease 2019 (COVID-19)

Abstract: The novel coronavirus (2019-nCoV) is spreading very fast in Hubei Province of China. As of February 14, 2020, 51,986 confirmed cases (including laboratory-confirmed cases and clinically-confirmed cases) were reported in Hubei Province, and 1,318 of them died. Respiratory droplets and contact transmission are considered to be the most important routes of transmission of 2019-nCoV, but do not fully account for the occurrence of all coronavirus disease 2019 (COVID-19) cases, previously known as novel coronavirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
300
1
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(324 citation statements)
references
References 0 publications
8
300
1
15
Order By: Relevance
“…In SARS‐CoV and MERS‐CoV infected patients, intestinal infections are very common 6,7 . Results have now confirmed the presence of the live virus in stool samples from patients with COVID‐19, 8 which means that stool samples may contaminate hands, food, and water, and may cause infection by invading the mouth, respiratory mucosa, and conjunctiva. We report the detection method of 14 cases with confirmed COVID‐19 infection admitted to hospitals in Jinhua, aiming to investigate the other possible transmission route of this virus.…”
Section: Introductionmentioning
confidence: 81%
“…In SARS‐CoV and MERS‐CoV infected patients, intestinal infections are very common 6,7 . Results have now confirmed the presence of the live virus in stool samples from patients with COVID‐19, 8 which means that stool samples may contaminate hands, food, and water, and may cause infection by invading the mouth, respiratory mucosa, and conjunctiva. We report the detection method of 14 cases with confirmed COVID‐19 infection admitted to hospitals in Jinhua, aiming to investigate the other possible transmission route of this virus.…”
Section: Introductionmentioning
confidence: 81%
“…The indirect transmission pathway, envisioned as a patient's bodily uids-HITES-hands-mucous membrane nexus, is supported by experimental transmission studies in animal models 28 and by the results of investigations of the contamination of HITES with SARS-CoV-2 RNA in healthcare settings 25,[29][30][31] . The detection of infectious SARS-CoV-2 in patient feces 32,33 , together with the data on survival of SARS-CoV-2 in fecal suspensions 20,21 , suggest that a fecal/oral or fecal/respiratory route of transmission is possible. Zang et al 34 , upon being unable to recover infectious SARS-CoV-2 from RNA-positive human fecal samples, have argued that the virus is rapidly inactivated by simulated human colonic uid.…”
Section: Discussionmentioning
confidence: 98%
“…Asymptomatic patients were also found to have nasopharyngeal viral loads similar to symptomatic patients [23]. Additionally, Y. Zhang et al found live virus in stool samples [24]. Zhou and colleagues have reported positive virus results from both oral swabs and bronchoalveolar lavage samples, while bronchoalveolar lavage samples yielded higher viral copies [25].…”
Section: What Is the Duration Of Viral Shedding?mentioning
confidence: 97%